Poor penetration of cefcapene into aqueous humor after oral administration of cefcapene pivoxil to patients undergoing cataract surgery. Issue 2 (February 2020) - Okamoto, Koh; Asano, Shotaro; Yamamoto, Takehito; Toyono, Tetsuya; Yamaguchi, Ryo; Okada, Yuta; Okugawa, Shu; Suzuki, Hiroshi; Moriya, Kyoji; Aihara, Makoto
Abstract: Objectives: Studies on the penetration of orally administered cephalosporins to the aqueous humor are scarce. Therefore, in this study, we determined the concentration of cefcapene, a third-generation cephalosporin administrated orally as pivalate ester (cefcapene pivoxil), in the aqueous humor of patients undergoing cataract surgery to assess its potential for preventing postoperative endophthalmitis. Methods: Forty-four patients were administered a single dose of 100 mg cefcapene pivoxil preoperatively. Blood and aqueous humor samples were obtained at the time of surgery, and cefcapene concentrations were measured using ultra-performance liquid chromatography with tandem mass spectrometric detection. Results: The samples were obtained from 41 eyes of 39 patients (two patients underwent surgery in both eyes). The median cefcapene concentrations in the aqueous humor after 1–2 h, 2–3 h, and later than 3 h were 8.3, 18.4, and 23.7 ng/mL, respectively. The median cefcapene concentrations in serum after 1–2 h, 2–3 h, and later than 3 h were 198.5, 287.2, and 170.3 ng/mL, respectively. Aqueous humor penetration of cefcapene after 1–2 h, 2–3 h, and later than 3 h was 4.1, 7.9, and 13.5% respectively. Conclusions: Aqueous humor penetration of orally-administered cefcapene pivoxil in patients undergoing cataract surgery was poor. Therefore, cefcapene pivoxil was unlikely to be effective for preventing endophthalmitis after cataract surgery.